PENINGKATAN PENGUASAAN PELAJARAN IPA SISWA MI MELALUI METODE PRAKTIKUM : (Studi Implementasi di MI Al-Mustofa Mojokerto) - Nur Laili Agustina; Imam Muslih (Kampus Akademik Publiser, 2024)
The practical method was theoretically proposed by researchers as an effective method for improving students' mastery of science or science lessons. This research aims to prove whether this theory applies to MI students. Because, compared to middle or upper level students, MI students tend to need detailed direction and explanation of a lesson. This tendency is contrary to the principle of the practicum method which provides direct experience of the subject matter, instead of conveying it through teacher explanations. In order to provide proof, this research was conducted through an implementation study at one of the MIs, namely MI Al-Mustofa Mojokerto. The research was conducted using a qualitative approach using a descriptive case study type. There are three data extracted in this research, namely data about the teaching and learning process, reasons and objectives in choosing practicum methods, and the impact of learning. This data was extracted through observation and interview techniques and analyzed descriptively-qualitatively. The research results show that the implementation of the practicum method in science subjects at MI Al-Mustofa is recognized by teachers and students as being able to improve students' abilities. Implementationally, the practicum method is balanced with detailed direction and explanation from the teacher. Apart from that, not all science material for MI students is considered by teachers to be able to be taught through practicum methods. Only lessons that really relate to a 'finished' tool can be taught through the practical method. This shows that there are distinctive characteristics in the use of effective practicum methods for MI students.